Enhancing Government Effectiveness: Human Resource Development in Village Administration - Hastuti, Tri Puji; Aswan, Mukhamad Kholil (MultiTech Publisher, 2025)
This research aims to examine the human resource development strategies implemented in the local village administration of Padaan, Pabelan Subdistrict, Semarang Regency, and their impact on the effectiveness of governance. Using a qualitative research approach, the study employs interviews, document analysis, and direct observations to gather insights from local government officials, village leaders, and community members. The findings reveal that while there are efforts to improve human resource capabilities, challenges such as limited professional development opportunities, inadequate training programs, and lack of clear career progression hinder the full potential of the local administration. The study contributes to the understanding of rural governance by highlighting the critical role of human resource development in enhancing governmental effectiveness and providing a foundation for future policy reforms. The originality of this research lies in its focus on a specific rural administrative context, offering practical recommendations for improving human resource strategies in similar settings. This research underscores the importance of comprehensive human resource management in driving local governance efficiency and providing a model for other rural areas to strengthen their administrative practices